Application of non-invasive prenatal testing in screening chromosomal aberrations in pregnancies with different nuchal translucency cutoffs - Yong Xu; Siqi Hu; Liyuan Chen; Ying Hao; Hu Zhang; Zhiyong Xu; Weiqing Wu; Liyanyan Deng (Molecular Cytogenetics, 2023)
Abstract Objective To investigate the efficiency of non-invasive prenatal testing (NIPT) in cases with different cutoffs of nuchal translucency (NT). Methods The study retrospectively analyses pregnancies with NT ≥ 2.5 mm who underwent NIPT. Results of NT, NIPT, chromosomal diagnostic and pregnancy outcomes were collected. Results Study group was composed of 1470 single pregnancies, including 864 with NT 2.5–2.9 mm, 350 with NT 3.0–3.4 mm and 256 with NT ≥ 3.5 mm. Non-significant differences were found in the positive predictive value (PPV) of NIPT between different cutoffs of NT. There was one false positive case with NT 4.3 mm, screening for 47,XYY in NIPT showed normal in diagnostic testing. For cases with normal NIPT results, the residual risk is 1:20 (5%, 95%CI: 0.1–10.1%) in fetuses with NT 3.0–3.4 mm and 1:15 (6.5%, 95%CI: 1.4%-11.5%) in fetuses with NT ≥ 3.5 mm. These false negative cases included one trisomy 21, seven pathogenic CNVs, one uniparental disomy and one single gene disorders. Conclusion Our findings demonstrated that the PPV of NIPT for screening chromosomal aberrations were similarly in different NT cutoffs, while false positive case does exist. After normal in NIPT, risk for chromosomal aberrations remained, especially pathogenic CNV and even common trisomy. Therefore, prenatal diagnosis was recommended and CMA was suggested to apply in pregnancies with NT ≥ 3.0 mm.